Gold mining as a potential driver of development in Colombia: Challenges and opportunities. (20th October 2018) - Betancur-Corredor, Bibiana; Loaiza-Usuga, Juan Carlos; Denich, Manfred; Borgemeister, Christian
Abstract: The Colombian government included gold mining as one of the drivers of development for the period 2014–2018. Large-scale gold mining is expanding due mainly to international investors attracted by the government. Small-scale and artisanal mining is also expanding, mainly because of increasing gold prices. This expansion of gold mining activities can have considerable consequences for the environment, as it can lead to more pollution and environmental degradation, posing a threat to the natural ecosystems and the health of the communities living in gold mining areas. This literature review analyzes the main challenges of the gold mining sector in Colombia from the environmental and social perspective, as well as initiatives developed to cope with these challenges and the opportunities to carry out more sustainable gold mining activities in the country. The main environmental challenges of the gold mining sector in Colombia are the pollution of natural ecosystems through the generation of solid waste, emissions of mercury during gold amalgamation, and greenhouse gas emissions. To cope with these challenges, reclamation of waste deposits is being conducted through silviculture, agriculture and reforestation. Furthermore, mercury reduction technologies have been adopted in gold mining areas and trials for remediation of polluted ecosystems are being conducted. The main social challenges of the gold mining sector are high levels of poverty, illegality and violence of communities living in the gold mining areas, as well as high levels of informality of gold mining. To cope with these challenges, the communities are being actively involved in the reclamation schemes of gold mining companies in many areas of the country with the aim to restore their livelihoods and improve their wellbeing. Moreover, elements of corporate social responsibility are being implemented to compensate for the loss of livelihoods, health effects and other social consequences of gold mining activities. To achieve a more sustainable gold mining production in the country, it is necessary to develop a framework for sustainability assessments to support decision making in the sector. Efforts need to be made to improve resource-use efficiency and biodiversity protection. From the social perspective, corporate social responsibility practices should be strengthened, especially towards understanding the needs of the local communities and the creation of mechanisms of participation that could help to prevent social conflicts around gold mining areas.